Limits on WWγ and WWZ couplings from W boson pair production - Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alves, G; Amos, N; Anderson, E; Astur, R; et al. (1998)
The results of a search for W boson pair production in pp̄ collisions at √s = 1.8 TeV with subsequent decay to eμ, ee, and μμ channels are presented. Five candidate events are observed with an expected background of 3.1 ± 0.4 events for an integrated luminosity of approximately 97 pb-1. Limits on the anomalous couplings are obtained from a maximum likelihood fit of the ET spectra of the leptons in the candidate events. Assuming identical WWγ and WWZ couplings, the 95% C.L. limits are -0.62<Δκ<0.77 (λ = 0) and -0.53<λ <0.56 (Δκ = 0) for a form factor scale Λ= 1.5 TeV.